Clinical and diagnostic manifestations in women of reproductive age having both hyperthyroidism and hyperandrogenism - N. E. Akhundova (Акушерство, гинекология и репродукция, 2020)
Aim: to study the clinical and diagnostic manifestations of hyperandrogenism (HA) in women with subclinical thyrotoxicosis.Materials and methods. Sixty three hyperthyroid women with clinical manifestations of HA were examined. Of these, 17 patients (27.0 %) were diagnosed with hyperthyroidism and HA. The control group included 20 practically healthy women of the similar age (20–44 years old) with no signs of HA or other hormonal disorders. All women under observation (patients with thyrotoxicosis and HA syndrome and women from the control group) underwent a thorough clinical examination and were assessed for their hormonal status using biochemical assays. The levels of follicle-stimulating (FSH), luteinizing (LH), thyroid-stimulating (TSH) hormones, prolactin, estradiol (E2), estrone, and total testosterone (Ttotal) were measured as well as the levels of dehydroepiandrosterone- sulfate (DHEA-S), 17-hydroxyprogesterone (17-OHP), free triiodothyronine (T3free), free thyroxin (T4free), sex hormone binding globulin (SHBG), androstenedione, and antimullerian hormone.Results. Patients with hyperthyroidism and HA had significantly (р < 0.05) higher (than normal) levels of FSH, LH, LH/FSH, estrone, 17-OHP, Ttotal, androstenedione, DHEA-S, T3free , and T4free, as well as lower levels (р < 0,05) of TSH (0,390 ± 0,003 mU/ml), E2 (49.86 ± 4.00 pg/ml), and SHBG (49.65 ± 1.20 nmol/L). A course of pathogenetic therapy that included anti-hyperthyroidism treatment (tyrosol 5–10 mg/day for 3 months) followed by anti-HA treatment (combined oral contraceptives) resulted in significant (р < 0,05) reduction in LH, the LH/FSH ratio, estrone, 17-OHP, T3free, T4free, androstenedione (2.64 ± 0.008 ng/ml), DHEA-S (2.15 ± 0.14 pg/ml), Ttotal (1.32 ± 0.10 ng/ml) and in significant (р < 0,05) increase in E2 (69.46 ± 2.58 pg/ml), SHBG (59.59 ± 2.8 nmol/L), and TSH (1,79 ± 0,16 mU/ml).Conclusion. Combined pathogenetic therapy reduces the clinical manifestations of hyperthyroidism and HA syndrome, and restores the menstrual and reproductive functions of women.